Internalization of Wahdatul Ulum Values in Arabic Learning - Adhistia, Suci Kirani; Salamuddin (EDUTEC : Journal of Education And Technology, 2023)
The internalization of wahdatul'ulum values in learning seems to be urgently needed amid the rampant advances in the field of science that increasingly imitate the style of outside civilization that is easier to infer with the words freedom. So that the science that is developing today further distances man from his spiritual values, a lot of science no longer brings tranquility to the owner and even inventions can bring mudharat to people's lives. In addition, the more developed science the stronger this material assumption for fellow human beings occurs because science runs away from its spirit, where science is separated from religious values that cause aridity and emptiness for every claimant of knowledge and because it is far from teachings that rely on godhead. The purpose of this study is to describe and analyze how students change in learning after understanding the internalization of wahdatululum values that are included in learning. This research uses literature research methods, namely looking for data, collecting data, and analyzing data. The results of this study show that there are several ways to internalize the value of wahdatululum in Arabic learning, in order to foster confidence and awareness that all knowledge is basically a unity that originates and boils down to Allah Swt through His revelation either directly or indirectly. This research discusses the internalization of wahdatululum values in Arabic language learning. Arabic Language Education Study Program, Faculty of Tarbiyah and Teacher Training UIN North Sumatra Medan., The problem studied is how to internalize wahdatul'ulum values in Arabic language learning and what wahdatululum values are instilled in Arabic language learning.